2017
DOI: 10.18860/jip.v2i1.4248
|View full text |Cite
|
Sign up to set email alerts
|

HAEMAGLUTINATION OF Shigella flexneri SUBUNIT PILI PROTEIN 18 KDA AS A MOLECULE ADHESION IN MICE ENTEROCYTES

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…These cytokines have also been identified as the other cytokines inhibitor since it inhibits the myeloid cells' ability such as macrophages and dendritic cells to activate Th1 cells so that the cytokines production by Th1 cells is blocked. 12 Another possible cause of the decrease in IL-10 levels is the microorganisms burden, in this study was formed as pili protein along with adjuvant induction, was not high enough to increase the production of IL-10. As other studies explained that infections caused gramnegative bacteria, the microorganism burden can affect the IL-10 response.…”
Section: Discussionmentioning
confidence: 76%
“…These cytokines have also been identified as the other cytokines inhibitor since it inhibits the myeloid cells' ability such as macrophages and dendritic cells to activate Th1 cells so that the cytokines production by Th1 cells is blocked. 12 Another possible cause of the decrease in IL-10 levels is the microorganisms burden, in this study was formed as pili protein along with adjuvant induction, was not high enough to increase the production of IL-10. As other studies explained that infections caused gramnegative bacteria, the microorganism burden can affect the IL-10 response.…”
Section: Discussionmentioning
confidence: 76%
“…Based on research in 2017, the results showed that the S. flexneri pili protein subunit was able to cross-react with Omp S. flexneri with Molecular Weight (MW) 23 and 27 kDa, and could cross-react with the pili 18 kDa subunit; 23; 34; and 53 kDa S. flexneri [9]. Then from another study in the same year, it was also found that the 18 kDa S. flexneri pili subunit protein is an adhesive protein that can help attach the pili bacteria to the enterocyte cells of mice [10]. A 2018 study proved that β defensin in the serum, intestinal mucosa, and lungs of mice was increased by oral vaccination of the 18 kDa protein subunit S. flexneri pili for 4 weeks.…”
Section: Introductionmentioning
confidence: 97%